S-Ketamine oral thin film—Part 2: Population pharmacodynamics of S-ketamine, S-norketamine and S-hydroxynorketamine - Simons, Pieter; Olofsen, Erik; van Velzen, Monique; van Lemmen, Maarten; van Dasselaar, Tom; Mohr, Patrick; Hammes, Florian; van der Schrier, Rutger; Niesters, Marieke; Dahan, Albert (Frontiers in Pain Research, 2022)
Ketamine is a versatile drug used for many indications and is administered via various routes. Here, we report on the pharmacodynamics of sublingual and buccal fast-dissolving oral-thin-films that contain 50 mg of S-ketamine in a population of healthy male and female volunteers. Twenty volunteers received one or two 50 mg S-ketamine oral thin films in a crossover design, placed for 10 min sublingually (n = 15) or buccally (n = 5). The following measurements were made for 6 h following the film placement: antinociception using three distinct pain assay; electrical, pressure, and heat pain, and drug high on an 11-point visual analog scale. Blood samples were obtained for the measurement of plasma S-ketamine, S-norketamine, and S-hydroxynorketamine concentrations. A population pharmacodynamic analysis was performed in NONMEM to construct a pharmacodynamic model of S-ketamine and its metabolites. P-values < 0.01 were considered significant. The sublingual and buccal 50 and 100 mg S-ketamine oral thin films were antinociceptive and produced drug high with effects lasting 2–6 h, although a clear dose-response relationship for antinociception could not be established. The effects were solely related to the parent compound with no contribution from S-norketamine or S-hydroxynorketamine. S-ketamine potency was lower for antinociception (C50 ranging from 1.2 to 1.7 nmol/mL) than for drug high (C50 0.3 nmol/ml). The onset/offset of effect as defined by the blood-effect-site equilibration half-life did not differ among endpoints and ranged from 0 to 5 min. In conclusion, the 50-mg S-ketamine oral thin film was safe and produced long-term antinociception in all three nociceptive assays with side effects inherent to the use of ketamine. The study was registered at the trial register of the Dutch Cochrane Center (www.trialregister.nl) under identifier NL9267 and the European Union Drug Regulating Authorities Clinical Trials (EudraCT) database under number 2020-005185-33.